The prognostic value of the GPAT/AGPAT gene family in hepatocellular carcinoma and its role in the tumor immune microenvironment - Wen, Peizhen; Wang, Rui; Xing, Yiqun; Ouyang, Wanxin; Yuan, Yixin; Zhang, Shuaishuai; Liu, Yuan; Peng, Zhihai (Frontiers in Immunology, 2023)
Liver cancer is the sixth most frequently diagnosed cancer and the third leading cause of cancer-related death worldwide. Hepatocellular carcinomas are estimated to account for 90% of all liver cancers. Many enzymes belonging to the GPAT/AGPAT family are required for the synthesis of triacylglycerol. Meanwhile, the expression of AGPAT isozymes has been reported to be associated with an increased risk of tumorigenesis or the development of aggressive phenotypes in a variety of cancers. However, whether members of the GPAT/AGPAT gene family also influence the pathophysiology of HCC is unknown. Here, we explored the role of the GPAT/AGPAT gene family in HCC and developed a risk model for predicting the outcome of the disease. Predictive models for three genes—AGPAT5, LCLAT1, and LPCAT1—were constructed based on LASSO-Cox regression. The ICGC-LIRI dataset was used as an external validation cohort. Compared with low-risk patients, high-risk patients had shorter survival and higher risk scores. Multivariate Cox regression analysis showed that risk score was a meaningful independent predictor of overall survival (OS) after adjusting for confounding clinical factors (p < 0.001). The established nomogram combined risk score and TNM staging to accurately predict survival at 1, 3, and 5 years in patients with HCC, with AUC values of 0.807%, 0.806%, and 0.795%, respectively. This risk score improved the reliability of the nomogram and guided clinical decision-making. In addition, we comprehensively analyzed immune cell infiltration, response to immune checkpoint blockade, clinical relevance, survival, mutations, mRNA expression-based stemness index, signaling pathways, and interacting proteins relating to the three core genes of the prognostic model. In summary, we identified a novel risk profile based on the GPAT/AGPAT gene family for predicting the prognosis of patients with HCC and undertook a comprehensive bioinformatics analysis of the three core genes in the prognostic model, as well as a preliminary validation of the differential expression, oncological phenotype and potential downstream pathways of the three core genes by IHC, CCK-8, Transwell assay, and Western blotting. These results strengthen our understanding of the functions of members of the GPAT/AGPAT gene family and provide valuable insights for prognostic biomarker exploration and individualized treatment for HCC.